The 3 I’s of immunity and aging: immunosenescence, inflammaging, and immune resilience - Wrona, Marianna V.; Ghosh, Rituparna; Coll, Kaitlyn; Chun, Connor; Yousefzadeh, Matthew J. (Frontiers in Aging, 2024)
As we age, our immune system’s ability to effectively respond to pathogens declines, a phenomenon known as immunosenescence. This age-related deterioration affects both innate and adaptive immunity, compromising immune function and leading to chronic inflammation that accelerates aging. Immunosenescence is characterized by alterations in immune cell populations and impaired functionality, resulting in increased susceptibility to infections, diminished vaccine efficacy, and higher prevalence of age-related diseases. Chronic low-grade inflammation further exacerbates these issues, contributing to a decline in overall health and resilience. This review delves into the characteristics of immunosenescence and examines the various intrinsic and extrinsic factors contributing to immune aging and how the hallmarks of aging and cell fates can play a crucial role in this process. Additionally, it discusses the impact of sex, age, social determinants, and gut microbiota health on immune aging, illustrating the complex interplay of these factors in altering immune function. Furthermore, the concept of immune resilience is explored, focusing on the metrics for assessing immune health and identifying strategies to enhance immune function. These strategies include lifestyle interventions such as diet, regular physical activity, stress management, and the use of gerotherapeutics and other approaches. Understanding and mitigating the effects of immunosenescence are crucial for developing interventions that support robust immune responses in aged individuals.